The genetic analysis of meiosis in Drosophila melanogaster females - Hawley, R. Scott (Henry Stewart Talks, 2009)
Identification of genetic material, The central dogma of meiosis, Nondisjunction frequencies for the Drosophila genome, A revised view of meiosis, Chromosome segregation, A mutational approach to understanding the meiotic process, Development of tools to study meiosis in Drosophila females, The 1996 P element screen, Genes defined by our first large-scale screen for new meiotic mutants, The 2004 'FLP-FRT' screen, Germline clone screen, Achiasmate (nonexchange) segregations are preceded by heterochromatic pairings, Mtrm and Polo
Reviewed at 2018/05/31